Estimated frequency of B-chromosomes and population density of Astyanax scabripinnis paranae in a small stream - Porto-Foresti, Fábio [UNESP]; Oliveira, Claudio; Maistro, Edson Luis [UNESP]; Foresti, Fausto (Sociedade Brasileira de Genética, 1997)
Um estudo comparativo foi realizado em exemplares de Astyanax scabripinnis paranae, envolvendo a freqüência de indivíduos portadores de cromossomos B e a densidade populacional desta espécie em três trechos consecutivos do córrego da Cascatinha (Botucatu, SP). No primeiro trecho, a população foi estimada em cerca de 212 indivíduos e, entre os 35 espécimes cariotipados, 23 (65,7%) apresentaram um macrocromossomo B; no segundo trecho, a população foi estimada em cerca de 650 indivíduos e, entre os 20 espécimes cariotipados, 2 (10%) apresentaram um macrocromossomo B; no terceiro trecho, a população foi estimada em cerca de 107 indivíduos e, entre os 10 espécimes cariotipados, 1 (10%) apresentou um macrocromossomo B. Uma diferença significativa foi observada na freqüência do cromossomo B presente nas fêmeas (57,1%) em relação aos machos (8,7%) (P = 0,0001). Esses dados sugerem que a freqüência de cromossomos B e a densidade populacional não estão diretamente relacionadas. A hipótese de ocorrência de algum efeito adaptativo conferido pelos cromossomos B aos peixes do primeiro trecho do córrego da Cascatinha é apresentada e discutida

A study was made of the frequency of B-chromosomes and the population density of Astyanax scabripinnis paranae (Pisces, Characidae, Tetragonopterinae) from three stretches of the Cascatinha stream (Botucatu, SP). In the first stretch the population was estimated to be about 212 individuals and among 35 karyotyped specimens, 23 carried one macro B-chromosome; in the second stretch the population was estimated to be about 650 individuals and among 20 specimens karyotyped, two possessed one macro B-chromosome; in the third stretch the population was estimated to be about 107 individuals and among 10 specimens karyotyped, one carried one macro B-chromosome. A significant difference was observed in the frequency of macro B-chromosomes in females (57%) and males (8.7%) (P = 0.0001). These data suggest that the B-chromosome frequency and the populational density are not directly related. The hypothesis of the existence of some adaptive effect conferred by the B-chromosomes to the specimens from the first stretch of the Cascatinha stream is presented and discussed